An improved sliding window data compression algorithm based on the Lempel-Ziv data compression algorithm (magnetic recording) - Bender, P.E.; Wolf, J.K. (GLOBECOM '90 : IEEE Global Telecommunications Conference, 1990, and Exhibition. 'Communications: Connecting the Future' : 2-5 December 1990, 1990)
A data compression scheme which can improve the efficiency of the Lempel-Ziv data compression algorithm is presented. The proposed scheme is designed to save bits in specifying the length of the matching string. The scheme specifies the difference between the longest and the next shortest length. Since this difference is never greater than the length of the string, and often shorter, this scheme can never be less efficient than the scheme where the length itself is used in the codeword, and it is often more efficient. Curves comparing the compression efficiencies of the improved Lempel-Ziv algorithm, the Lempel-Ziv algorithm, and the Lempel-Ziv-Welch algorithm are given.< >